Transmission of Islamic Educational Values Through Local Wisdom in Malay Nusantara Oral Traditions - Hidayat, Rahmat; Mulyana, Rohmat; Salleh, Mohamad Johdi; Mahanum, Mahanum (Fitrah: Journal of Islamic Education, 2025)
The oral tradition of the Malay community in the Nusantara plays a central role in transmitting Islamic educational values across generations. Through mediums such as advisory pantun, gurindam, religious syair, customary proverbs, tunjuk ajar Melayu, as well as folktales and legends, values of faith, law, and morality are conveyed subtly yet profoundly in everyday life. This study aims to explore the transmission process of Islamic educational values embedded in Malay oral traditions, focusing on their meanings, functions, and contexts of delivery in Langkat Regency. A qualitative approach was employed, utilizing text analysis, interviews, and cultural observation. The findings reveal that oral tradition serves not merely as a medium of entertainment or literature but also as a deeply rooted instrument of da'wah and education within the local culture. The identified values include: (1) divinity (tawhid), (2) morality and social ethics, (3) patriotism, (4) love of knowledge and education, and (5) the sustainable preservation of ancestral culture. These findings highlight the successful acculturation between Islam and Malay culture and suggest that oral traditions can serve as a relevant and contextual model for character education in the modern era.